India in the early modern world economy: modes of production, reproduction and exchange - Washbrook, D (Cambridge University Press, 2007)
India played a leading role in the growth of the early modern world economy. Yet its historiography has been dominated by forebodings of the colonial conquest and decline, which were to overtake it at the end of the eighteenth century. This essay seeks to explore the strengths rather than weaknesses of the Indian economy between the sixteenth and eighteenth centuries when the goods which it produced were in heavy demand in Asia, Africa, Europe and the Americas. However, it also points to ways in which specific features of India's commercial development created vulnerabilities to conquest from overseas, which would be exploited later on.